Bariatric Surgery and the Incidence of Psoriasis and Psoriatic Arthritis in the Swedish Obese Subjects Study. Issue 12 (27th November 2017) - Maglio, Cristina; Peltonen, Markku; Rudin, Anna; Carlsson, Lena M.S.
Abstract : Objective: The aim of this study was to assess the effect of bariatric surgery (vertical gastroplasty, gastric banding, or gastric bypass) compared with usual care on the incidence of psoriasis and psoriatic arthritis (PsA) in the Swedish Obese Subjects study. Methods: This report includes 1, 991 subjects who underwent bariatric surgery and 2, 018 controls with obesity from the SOS study; none of them had psoriasis or PsA at baseline. Information about psoriasis and PsA diagnosis was retrieved through the Swedish National Patient Register and questionnaires. Results: During follow‐up for up to 26 years, bariatric surgery was associated with a lower incidence of psoriasis compared with usual care (number of events = 174; hazard ratio 0.65; 95% CI: 0.47‐0.89; P  = 0.008). Both smoking and a longer duration of obesity were independently associated with a higher risk for psoriasis. No significant difference was detected among the three surgical procedures in terms of lowering the risk of developing psoriasis. The association between bariatric surgery and psoriasis incidence was not influenced by baseline confounders. No significant difference in the risk of developing PsA (number of events = 46) was detected when comparing the surgery and the control groups. Conclusions: This study shows that bariatric surgery is associated with a lower risk of developing psoriasis compared with usual care.